Reverse logistics strategy that allows the recovery of bottles glass in optimal conditions for the Cauca Liquor Industry - Papamija Dorado, Ivan Dario; Estacio Estacio, Kevin Anthony; Mendoza Chacon, Jaime Humberto; Arciniegas, Nora Fernanda; Segura Mosquera, Juan Manuel (Ingeniería Solidaria, 2025)
Introduction: The article is the result of the research on reverse logistics strategies that allow the recovery of glass bottles in optimal conditions for the Cauca Liquor Industry, developed at the Fundación Universitaria de Popayán in 2024.Methods: The methodology began with a diagnosis of the use of glass containers in the liquor industry. Based on this analysis, strategies were developed to improve container recovery. Innovative technologies were studied, a collaboration with local communities was proposed, and transportation routes were optimized to ensure a more efficient collection process.Results: The study identified several key solutions. The importance of integrating technologies to facilitate the sorting and collection of glass containers was emphasized. The active involvement of local communities in the collection process was also highlighted. Additionally, the optimization of transportation routes contributed to more efficient management.Conclusions: This paper demonstrates that reverse logistics is essential for the sustainability of the I.L.C. Implementing strategies for the recovery and reuse of glass containers not only supports the circular economy but also reduces environmental impact.Originality: This study provides innovative solutions to a specific problem faced by the I.L.C., offering a unique approach to solving the glass container shortage.Limitation: The implementation of these strategies may face challenges related to available infrastructure and the collaboration of all involved stakeholders.
Keywords: costs; efficiency; reverse logistics; production; environmental impact